2018
DOI: 10.1111/1556-4029.13790
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Study of Carbon Monoxide Deaths in Scotland 2007–2016,

Abstract: Carbon monoxide (CO) intoxications are quite frequent in forensic toxicology. Using a sample of 209 CO-positive deaths in Scotland from 2007 to 2016, this study provides ranges of percentage CO saturations (%COHb) according to the CO source and examines any correlation with age, gender, alcohol, and preexisting disease. It also reports the full toxicological findings, including drug concentrations, in CO-positive cases. The highest numbers of fatalities involved males, occurred during autumn/winter, and the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 50 publications
(84 reference statements)
1
4
0
Order By: Relevance
“…Deaths occurred in all months, with the most occurring in winter (42%). This trend has been observed in many other studies [ 5 , 14 , 18 , 24 , 25 ]. High risk behaviours to keep warm in cooler months, such as using unventilated appliances to heat the home or running car engines inside enclosed spaces, such as garages, are likely factors here.…”
Section: Discussionsupporting
confidence: 86%
“…Deaths occurred in all months, with the most occurring in winter (42%). This trend has been observed in many other studies [ 5 , 14 , 18 , 24 , 25 ]. High risk behaviours to keep warm in cooler months, such as using unventilated appliances to heat the home or running car engines inside enclosed spaces, such as garages, are likely factors here.…”
Section: Discussionsupporting
confidence: 86%
“…36 CO is an oxygen antagonist, readily binding to haemoglobin to form carboxyhaemoglobin (COHb) preventing oxygen exchange with tissues. 68…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] CO is an oxygen antagonist, readily binding to haemoglobin to form carboxyhaemoglobin (COHb) preventing oxygen exchange with tissues. [6][7][8] Suicide by CO toxicity requires some level of premeditation and planning as occurred in Case 2 where the purchase of materials occurred the day before death with connection of a pipe to feed exhaust fumes into the vehicle cabin. 9 CO does not need to be directly piped into the cabin as the vehicle may be parked in an enclosed, confined space such as garage and allowed to run (as occurred in Case 1).…”
Section: Inhalation Of Gasmentioning
confidence: 99%
“…Although there was no change in the incidence of CO poisoning between 1992 and 2017, they reported that the risk of death decreased by 36%. Forés & Hamnett (2018) stated that deaths due to CO poisoning are more common in men than women since men are more in contact with CO. Mattiuzzi & Lippi (2020) , on the other hand, argued that although there was no difference in gender in terms of incidence, the death rate due to CO poisoning in men was twice that of women.…”
Section: Introductionmentioning
confidence: 99%